Effectiveness of computerized tomography in the management of right colon diverticulitis treatment (Annals of Medical Research, 2021)
Aim:Symptoms of right colon diverticulitis may mimic acute appendicitis. Therefore, most of these patients undergo unnecessary surgical intervention due to suspicion of appendicitis. The aim of this study was to evaluate the clinical and treatment results of our patients with right colon diverticulitis.Material and Methods: Between January 2016 and December 2020, demographic and clinical data of 15 patients diagnosed with right-sided colon diverticulitis among 104 patients with colonic diverticulitis were retrospectively analyzed and radiological evaluation and clinical findings were recorded.Results: Fifteen patients were included from in the study. The mean age of the patients was 37.73, 9 (60%) were female and 6 (40%) were male. The duration of symptoms before hospitalization was 1-4 days, with an average of 2.2 days. Generally, 66.6% of the patients had fever, 46.6% had nausea, 33% had diarrhea, 73% had pain in the lower right abdomen, and 27% had general abdominal pain at the time of admission. Leukocytosis was detected in 86.6% of all patients. High CRP levels were found in all patients (100%).Since two patients had an ultrasound image compatible with acute appendicitis, surgery was performed without computed tomography. In these two patients, Hinchey-1b cecum diverticulitis was found as a surgical finding. Computed tomography with oral and intravenous contrast was used for all other patients. Diagnostic laparoscopy was performed on the computed tomography of a patient after suspicious findings accompanying cecum diverticulitis. In one patient, diverticulitis in the cecum and abscess in the right colon medial was observed (Hinchey-2). This patient underwent percutaneous drainage and IV antibiotherapy accompanied by interventional radiology, and the treatment was successful. In one patient, right hemicolectomy and ileocolic anastomosis were performed due to complicated right colon diverticulitis and acute abdomen (Hinchey 3). Although ultrasound evaluation was performed on all patients, the diagnosis of diverticulitis could not be made clearly for 8 (53.3%) patients. According to localization, 66.6% of patients had diverticulitis in the right colon (except cecum) and 33.3% had diverticulitis in the cecum.Conclusion: In experienced hands, ultrasonography can make it easier to differentiate diverticulitis from acute appendicitis, however, in suspected cases, CT is of great importance to determine the correct diagnosis and suspected complications necessary to choose the right treatment. Acute appendicitis and right colon diverticulitis can be confused, especially cecal diverticulitis, and uncomplicated cecal diverticulitis can usually be managed conservatively.